Plan de negocios, para el mejoramiento de la rentabilidad de la inversión de una sucursal de Madoba en la ciudad de Manta, Provincia de Manabí año, 2014 - Montes Acosta, Lilia Marisol (2015)
This research was conducted in city of Manta which has 226,477 inhabitants, was to market research, technical, organizational, economic, and financial evaluation projected 5-year term in order to give the investor a tool support for establishment of a branch in the city Madoba Manta, and it will allow the company to venture into a new market. For registration information, a questionnaire was used to survey the inhabitants of the city of Manta to determine their judgment of quality, prices, Purchase Electronics. The net present value had a positive value of $ 477.192,88 which means the liquid return generated by the project updates. Therefore the project is feasible. The internal rate of return is 65% which was higher than the market interest rate therefore the project is feasible and viable from the economic point of view. The cost benefit ratio is determined by dividing net profit for the interest rate of the bank loan obtaining the target of 1, 30. This shows that for every dollar invested returns one U.S. 0.30 dollar of profit, therefore the project is financially feasible.